Zakat, Infaq and Charity as Instruments of Community Empowerment - Dede Fadillah (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This study examines the role of zakat, infaq, and sadaqah (ZIS) as instruments of community empowerment by developing an integrative framework that links economic, social, and institutional dimensions within a holistic empowerment ecosystem. Methods: A qualitative approach was employed through a systematic literature review (SLR) following the PRISMA protocol. Data were collected from peer-reviewed journal articles, institutional reports, and policy documents. Thematic analysis was used to identify recurring patterns and develop theoretical propositions. Key Findings Three key findings emerged. First, productive ZIS programmes supported by mentoring, training, and market access generate more sustainable empowerment outcomes than consumptive distribution. Second, effective ZIS-based empowerment is multidimensional, requiring the simultaneous strengthening of economic capacity, social capital, spiritual well-being, institutional governance, and human resource quality. Third, integrating ZIS with Islamic finance institutions, government programmes, and local economic networks significantly enhances empowerment outcomes. Contribution: Zakat institutions should adopt multidimensional evaluation indicators beyond income-based measures, while policymakers should integrate ZIS into broader development and fiscal frameworks. Conlusion: This study proposes an integrative ZIS empowerment ecosystem model and highlights educational inequality, community resilience, and institutional integration as key determinants of sustainable empowerment.